(3PNjQI GdeYGO aj TQM GdEQTGOs - (3GdSHRhGQj, GdNQSGfj, eMeO HGbQ Hf eMeO eDef, J (B1090(3g`s
(3ChdgG (B:s
(3bGd (B-(3bOS SQg(B- (3cJGH GdWgGQI hajg ebOeI hKdGKI eUGOQ hNGJeI CeG GdebOeI aajgG aUdGf(B...s
(3BNQgG (B:s
...(3hGdMce ajeG bHd GdKdGKI ehGab ddbhGYO ZjQ eMJGL Edi GdOdjd hCeG GdGSJMHGH ajeG HYO GdKdGKI adYd gPG GdeSJfO jcaj ajg hEf cGf VYjaG(B...s
(3JHUQI GdYfhGf (B:s
(3PNjQI GdeYGO aj TQM GdEQTGOs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B6(3,U(B48s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B157s
(3EjVGM Gdecfhf(B:(3L(B1(3,U(B542s
Keywords: (3abg GdePGgH GdCNQis